2012
DOI: 10.1130/g32737c.1
|View full text |Cite
|
Sign up to set email alerts
|

Early Cambrian metazoans in fluvial environments, evidence of the non-marine Cambrian radiation: COMMENT

Abstract: Early Cambrian metazoans in fl uvial environments, evidence of the non-marine Cambrian radiation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…After extensive and detailed examination of bedding tops and cross‐sections in the southern Marble Mountains, this study identified no evidence of fossil traces in the distal fluvial environment. Such a conclusion reinforces the hypothesis that the reported trace fossils represent marine organisms that burrowed older fluvial sediments during periods of marine flooding (Davies & Gibling, ; McIlroy, ) and emphasizes the importance of gathering detailed architectural analysis and palaeoenvironmental constraints when assessing the habitability of distal terrestrial environments. Near the coastline, braid deltas (McPherson et al ., ) form tidally influenced areas of stagnant water that interfinger with the fluvial system and may harbour life (e.g.…”
Section: Discussion: Depositional System Synthesissupporting
confidence: 83%
“…After extensive and detailed examination of bedding tops and cross‐sections in the southern Marble Mountains, this study identified no evidence of fossil traces in the distal fluvial environment. Such a conclusion reinforces the hypothesis that the reported trace fossils represent marine organisms that burrowed older fluvial sediments during periods of marine flooding (Davies & Gibling, ; McIlroy, ) and emphasizes the importance of gathering detailed architectural analysis and palaeoenvironmental constraints when assessing the habitability of distal terrestrial environments. Near the coastline, braid deltas (McPherson et al ., ) form tidally influenced areas of stagnant water that interfinger with the fluvial system and may harbour life (e.g.…”
Section: Discussion: Depositional System Synthesissupporting
confidence: 83%
“…Our current understanding of the ichnological record reveals that arthropods were the earliest pioneer animals to make forays onto land. Evidence for sporadic excursions onto subaerially exposed substrates by marine-dwelling arthropods can be witnessed in Cambrian and Ordovician successions worldwide, where sedimentological evidence proves that trackwayhosting strata were deposited in littoral environments, often demonstrably within metres of the marine shoreline (MacNaughton et al 2002;Collette et al 2010;Davies et al 2011a;Davies & Gibling, 2012;McIlroy, 2012;Minter et al 2016a;MacNaughton et al 2019;Shillito & Davies, 2019a, b). In younger strata, deposited around the Silurian-Devonian boundary, unequivocal instances of fully non-marine trace fossil communities occur (Minter et al 2016b(Minter et al , 2017Buatois & Mángano, 2018); their environmental preferences demonstrated by close association with diagnostic non-marine sedimentary phenomena including palaeosols, certain fluvial architectural styles, and in situ plant or root fossils (e.g.…”
Section: Terrestrialization and The Tumblagooda Sandstonementioning
confidence: 99%
“…Notwithstanding, the absence of rooted vegetation on the Earth's surface during the Meso-and Neoproterozoic should have exerted a marked influence on the development of continental depositional systems (Davies and Gibling, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On the current Earth's surface, the stabilising influence of vegetation controls the intensity and the rate of weathering, and rates of sediment erosion, transport and deposition. The absence of the stabilising influence of vegetation during the Precambrian might suggest the development of continental sedimentary systems that differed considerably to those that post-dated the evolution of land plants (Davies and Gibling, 2012). Thus, it seems reasonable to believe that in the Precambrian, a bare land surface might have encouraged the mobilisation of sand-grade sediment by the wind and the construction and accumulation of large aeolian systems, which might be expected to develop in more widespread environments and climates than in postvegetation landscapes.…”
Section: Introductionmentioning
confidence: 99%